(3eONd UfGYI GdUabGJ GdYGdejI aj YGde jehL HGdJfGaSjIs - (3YGWa LGHQ Wg(B, (3YHO GdQMjes ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3EOGQI GdJaGhV GdOhdj eONd UfGYI GdUabGJ GdYGdejI aj YGde jehL HGdJfGaSjI(B/(3GdJaGhV hGdUabI GdYGdejI(B/(3UfY GdUabGJ aj HjFI GLfHjI(B/(3ehGLgI eTcdI GNJdGa GdKbGaGJ(B/(3JMOjO GdGOjhdhLjI aj UfGYI GdUabGJ GdYGdejI(B/(3GdeaGhVGJ hGdHjQhbQGWjI GdGLfHjI(B/(3GdJaGhV hcja JJYGed eY GdMcheGJ hGdbhGfjjf(B/(3GdeaGhVGJ hfbd GdGehGd(B/(3GdYhOI eQI GNQi Gdi GdJaGhV(B/(3GdJaGhV ef GLd GdeUGdM GdeTJQcI(B/(3GdefXeGJ GdeUQajI hGOGQI GdJaGhV s
(3HjHdjhZQGajG U(B. s
Keywords: (3GOGQIs; (3GdefGbTGJ GdOhdjI s; (3GdhSGWIs; (3eaGhVGJs